The Effects of Rewarding System on Employee Turnover - John Kanyambo; Bogere Mohammed (Randwick International of Social Science Journal, 2020)
This study examined the effects of retention strategies on employee turnover taking a case of Urwego Opportunity Bank in Rwanda. The specific research objectives are: to identify the effects of reward on employee turnover and to analyze the effects of training on employee turnover. A descriptive research design was used where both qualitative and quantitative approaches were adopted.The target population was 250 employees and authorities of Urwego Opportunity Bank while 138 sampled populations was calculated using Slovin’s formula. The study set to use simple random sampling techniques in order to distribute research instruments. Finding on contribution indicated by regression model, a unit increase in a unit increase in Rewarding systems variable would cause an increase of 0.260(26.0 %) on employee turnover at Urwego.Finding also show that Rewarding systems posted ( t=2.357), this was greater 1.96 and sig = 0.002, so this clearly shows that the variable is significant since the sig value is less than 0.05.Conclusion : Employee retention strategies are statistically significant correlated with the reduction of employee turnover among workers at Urwego Opportunity Bank-Rwanda. Important and crucial it will affect an employee’s decision for leaving the organization. The study recommends that managers should provide trainings and copy with elements that stimulate the spirit of abandonment. Workers must have enough professional development workshops to ameliorate their knowledge and experience.